"أثر تخطيط المسار الوظيفي على أداء العاملين دراسة حالة موظفي جامعة ""حمه لخضر""بالوادي " - رانيا, مباركي; يمينة, مهشي (University of eloued جامعة الوادي, 2020)
هدفت هذه الدراسة إلى التعرف على أثر تخطيط المسار الوظيفي على أداء العاملين ، حيث كان إسقاط الجانب التطبيقي على موظفي جامعة الشهيد "حمه لخضر" بالوادي , واعتمدنا في هذه الدراسة على المنهج الوصفي التحليلي في جمع المعطيات والبيانات المتعلقة بالظاهرة موضوع البحث، ولتحقيق هذا الهدف استخدمنا الاستبيان كأداة للدراسة وتم توزيع استمارة الاستبيان داخل الجامعة على عينة مقدارها 50 موظف ، وقد اعتمدنا في تحليل بيانات الاستبيانات على برنامج الحزمة الإحصائية للعلوم الاجتماعية (SPSS)، برنامج معالج الجداول Excel ولاختبار الفرضيات اعتمدنا المتوسطات الحسابية، استخدام الانحراف المعياري، اختبار تحليل التباين الأحادي(One Way Anova)، كما تم استخدام أساليب الانحدار والارتباط لإثبات وجود علاقة بين متغيرات الدراسة، وفي الأخير خلصت الدراسة إلى أن تخطيط المسار الوظيفي عامل فعال في الجامعة، إذا يمثل الركيزة الأساسية في تطوير وتحسين أداء القوى العاملة.This study aimed to identify the impact of career planning on the performance of employees, as the applied aspect was dropped on the employees of the University of Al-Shaheed "Hama Al-Akhdar" in the valley, and we relied in this study on the descriptive analytical approach. In collecting data and data related to the phenomenon in question, and to achieve this goal, we used the questionnaire as a study tool that was distributed within the university to a sample of 50 employees, In analyzing the questionnaire data, we relied on the Statistical Package for Social Sciences (SPSS), and the Excel spreadsheet program, and to test the hypotheses we relied on the arithmetic means, the standard deviation, the One Way Anova test, regression and correlation methods were used to prove the existence of a relationship between the study variables. The study concluded that career path planning is an effective factor in the university, as it represents the mainstay in developing and improving the performance of the workforce.
مذكرة ماستر ادارة اعمال
Keywords: التخطيط، المسار الوظيفي،تخطيط المسار الوظيفي , التدريب والتكوين , الحوافز والاجور, الترقيات , الأداء، أداء العاملين; Planning , Career path, career path planning, training and training, incentives and wages, promotions, Performance, Staff performance.